2019
DOI: 10.1371/journal.pmed.1002766
|View full text |Cite
|
Sign up to set email alerts
|

Independent and combined effects of improved water, sanitation, and hygiene (WASH) and improved complementary feeding on early neurodevelopment among children born to HIV-negative mothers in rural Zimbabwe: Substudy of a cluster-randomized trial

Abstract: BackgroundGlobally, nearly 250 million children (43% of all children under 5 years of age) are at risk of compromised neurodevelopment due to poverty, stunting, and lack of stimulation. We tested the independent and combined effects of improved water, sanitation, and hygiene (WASH) and improved infant and young child feeding (IYCF) on early child development (ECD) among children enrolled in the Sanitation Hygiene Infant Nutrition Efficacy (SHINE) trial in rural Zimbabwe.Methods and findingsSHINE was a cluster-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 47 publications
2
41
0
1
Order By: Relevance
“…Among 5280 enrolled pregnant women, there were 738 HIV‐exposed and 3989 HIV‐unexposed live births; of these, 323 HIV‐exposed and 1655 CHU were assessed in the ECD sub‐study at two years of age (Figure ). Mothers of children included in the ECD sub‐study were about two years older compared to mothers of those not included; other baseline characteristics were broadly similar (as reported previously and shown in Table ).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Among 5280 enrolled pregnant women, there were 738 HIV‐exposed and 3989 HIV‐unexposed live births; of these, 323 HIV‐exposed and 1655 CHU were assessed in the ECD sub‐study at two years of age (Figure ). Mothers of children included in the ECD sub‐study were about two years older compared to mothers of those not included; other baseline characteristics were broadly similar (as reported previously and shown in Table ).…”
Section: Resultssupporting
confidence: 60%
“…Overall, 5280 pregnant women were recruited from 211 clusters at a median gestational age of 12.5 weeks and randomized to standard‐of‐care (SOC); IYCF (20 g small‐quantity lipid‐based nutrient supplement (SQ‐LNS) per day from six to eighteen months of age, complementary feeding counselling); WASH (ventilated improved pit latrine and 2 hand‐washing stations, monthly liquid soap and chlorine, a play‐space to separate children from livestock and to reduce geophagia, hygiene counselling); or IYCF plus WASH (all interventions). The primary findings and ECD findings among a subgroup of children at 24 months have been reported previously, stratified by maternal HIV status .…”
Section: Methodsmentioning
confidence: 61%
See 2 more Smart Citations
“…We calculated pooled effect sizes if at least five studies reported an intervention versus control group comparison in any category of intervention (eg, nutritional supplementation and promotion of responsive care and learning opportunities). We applied the same criterion to stratified 29 Ong et al 37 Jeon et al 41 Lind et al 31 Rosado et al 15 Oelofse et al 52 Nahar et al 48 Smuts et al 62 Husaini et al 50 Phuka et al 21 Maleta et al 17 Krebs et al 54 Bauserman et al 55 Faber et al 14 Hess et al 16 Dewey et al 20 77 Luby et al 23 Stewart et al 22 Gladstone et al 61 Lees et al 80 Hallamaa et al 82 Tomlinson et al 78 Tumwine et al 79 Dewey et al 20 Adu-Afarwuah et al 18 Ashorn et al 19 Zhang et al 59 Thomas et al 60 Gowachirapant et al 51 Hamadani et al 35 Jacobson et al 58 Schmidt et al 53 Hanieh 36 Zhu et al 56 Nguyen et al 34 Christian et al 40 Gonzalez-Casano 87 Tofail et al 49 In utero 3 6 9 12 15 18 Months Years 64 Nahar et al 48 Hamadani et al 70 Tofail et al…”
Section: Data Collection and Analysismentioning
confidence: 99%